Pengembangan Sistem Informasi Pengajuan Perbaikan Sarana Prasarana Teknologi Informasi Berbasis Web Studi Kasus Pada RSUD Dr. Saiful Anwar Kota Malang - Hanif Rafidi; Satrio Agung Wicaksono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
RSUD Dr. Saiful Anwar is a local hospital located in the center of Malang. The hospital already using information technology infrastructure for improving service to all unit. When problem occurred to IT infrastructure, there's procedure for repairs submission with ITIKOM unit as the person in charge of IT development. Based on interview, process of repairs submission has problem with monitoring the repairs process from ITIKOM technician, and the submitting process is still done by manually using a form sheet. These problems, can be solved by developing a web-based information system for monitoring the repair process and submitting process. The development for this system using Rational Unified Process (RUP), which has 4 phases inception, elaboration, construction, and transition. This research for development system produces requirement analysis, business modelling, design, implementation and testing. There are 2 type of system testing, validation testing that produces 100% for all system features and user acceptance testing result are 85.53% from all system actors, this concluded system has been well developed and fulfill user requirements.